Numerical solution of the hydrodynamics problem with a curved interphase boundary - Rukavishnikov, Aleksey Viktorovich (Computational Continuum Mechanics, 2013)
In this paper, we develop an approximate method and perform the numerical analysis of the mathematical model, obtained by sampling in time and linearizing the problem of a two-phase viscous fluid flow. We assume that the fluid is incompressible, phase mixing is absent, and the interphase boundary varies with time. The problem is formulated based on incompressible Navier-Stokes equations taking into account these constraints.
Keywords: Navier–Stokes equations; curvilinear interphase boundary; discontinuous coefficients